Being assigned a clinical nurse specialist is associated with better experiences of cancer care: English population‐based study using the linked National Cancer Patient Experience Survey and Cancer Registration Dataset. (26th July 2021) - Alessy, Saleh A.; Lüchtenborg, Margreet; Rawlinson, Janette; Baker, Matthew; Davies, Elizabeth A.
Abstract: Objective: This study aimed to examine whether being given the name of a clinical nurse specialist (CNS) is associated with better cancer patients' experiences across different points along their cancer care pathway. Methods: We identified 100, 885 colorectal, lung, breast and prostate cancer patients who responded to the National Cancer Patient Experience Survey between 2010 and 2014. We compared experiences of four key aspects of cancer care among patients who reported being given a CNS name with those who did not, adjusting for age, sex, socio‐economic deprivation, ethnicity, route to diagnosis and disease stage. Results: Across all cancers, patients who reported being given the name of a CNS reported better experiences with involvement in treatment decisions, care coordination, treatment with more respect and dignity, and overall care experience. Experience of being involved in treatment decisions was the aspect of care most strongly associated with being given a CNS name (colorectal: OR 2.69, 95% CI: 2.45–2.96; lung: OR 2.41, 95% CI: 2.07–2.78; breast: OR 2.68, 95% CI: 2.47–2.92; and prostate: OR 2.11, 95% CI: 1.92–2.32). Conclusion: These findings may provide new evidence of the vital contribution CNS make to cancer care and suggest their input and support should be available to all patients after the diagnosis.